Memahami Keterbukaan Komunikasi Antar Pribadi Dalam Percakapan Online - Kasanah, Uswatun (Universitas Semarang, 2011)
The study aims to find the openness of interpersonal communication and process of exchange of stimulation in online conversation of Facebook social network Sites among students of Communication Science Semarang of University. The theory used in the study is Technological Determinism Theory which states that the changes that occur in a variety of ways to communicate will also make up the existence of mankind itself. The study can it is concluded that the openness of interpersonal communication in online conversation is open wide among students of Communication Science. Since Facebook overcomes the limitations of distance and physical and it is possible to the conversations is far more familiar than the face to face communication. It means that the users of chatting facility do not hesitate to open their selves and talk about serious matter of their lives.